Youth co-production for sustainable engagement and empowerment in health (YiPEE): protocol for a cluster-randomised controlled trial of an intervention for mental health promotion among adolescents in schools in Chennai, India - Josefien van Olmen; Pilvikki Absetz; Mark Tomlinson; Carina King; Edwin Wouters; Josefien van Olmen; G J Melendez-Torres; Jeroen De Man; Stefan Swartling Peterson; Suresh Kumar; Mariam Claeson; Monika Martens; et al. (BMJ Open)
Introduction Adolescence is a time of rapid physical, social and psychological development and many risk factors for mental disorders have their roots in this age period. Primary prevention through school platforms has been extensively used and evaluated, but many interventions have poor uptake, high dropout and limited long-term sustainability. Mental health is a complex phenomenon and may be best supported through multicomponent interventions that more holistically consider inner, social and environmental levels. Character education-focused interventions are effective for improving adolescent psychosocial functioning and mental well-being. Therefore, an intervention that focuses on developing these strengths and is delivered within a school environment, through an adolescent-informed approach using creativity-focused components, has the potential to improve adolescent mental health and well-being.Methods and analysis This protocol describes the YiPEE cluster-randomised controlled trial with concurrent mixed-methods process evaluation and economic evaluation, which aims to determine the impact of a multilevel multicomponent intervention in schools in Chennai, Tamil Nadu, India. Clusters—defined as schools which include Grades 6–8 (ages 11–16 years), will be randomised to intervention (n=15) or control (n=15). The intervention consists of: an 8-week classroom-based component, a 12-week teacher-focused component and a board comprising members from across the whole school. All children attending Grade 7 (aged 12–15) will be exposed to the classroom component, and teachers who actively teach Grade 7 will be invited to participate in the teacher component. Within schools, students for the individual-level evaluation will be included if they are: (1) aged 12–15 years; (2) currently attending Grade 7; (3) competent to give consent and (4) have a legal guardian competent of giving consent. We aim to sample a minimum of 100 students from each school (n=3000). All teachers of Grades 6–8 will be recruited for the evaluation. The primary outcome is symptoms of anxiety and depression measured using an abbreviated version of the UNICEF MMAPP tool. The primary analysis will be intention-to-treat, comparing the mean change in mental health score between baseline and endline, between intervention and control clusters. In addition, we will record school monitoring data (student attendance, student grades). Individual interviews with students and teachers, focus group discussions with school staff, and ethnographic observations will provide data for the process evaluation. For the economic evaluation, the combined direct and non-direct costs will be compared with changes in mental health in the intervention arm.Ethics and dissemination The trial is approved by the Ethics Council of the Schizophrenia Research Foundation, India, with approval number EC/NEW/INST/2023/TN/0329. We plan to publish the main impact, process and economic evaluation results as academic publications in international peer-reviewed journals in 2026.Trial registration number Clinical Trials Registry—India (CTRI/2024/07/070949).